Modeling Price Volatility and Supply Response of Beef in Indonesia - Komalawati Komalawati; R. W. Asmarantaka; R. Nurmalina; D. B. Hakim (Tropical Animal Science Journal, 2019)
Beef is one of the strategic livestock commodities in Indonesia. As demand increases, the price of beef increases and tends to be volatile. The increased volatility in beef prices could influence production decision and the supply of beef. This study aimed to investigate the price volatility and the impact of price volatility on the supply response of beef in Indonesia. This study used secondary data obtained from various related institutions. Volatility was estimated using the GARCH (p,q) model and the supply response model using OLS model. The empirical results indicated that among the estimated GARCH models, the GARCH (2,3) seemed to be particularly appropriate to describe the beef price supply response. Beef price volatility in Indonesia was found to be low and persistent in the long run. Price uncertainty appeared to have a substantial negative effect on Indonesian beef production. The slow adjustment of farmers to demand and supply shocks indicate the importance of import as a temporary policy to fulfill the demand of beef in the short and medium-run.